Notary's Principle of Prudence in Credit Guarantees in Banking - Nirwana, Erza Aulia; Hafidz, Jawade; Arifulloh, Achmad (TABELLIUS: Journal of Law, 2026)
This research is motivated by the great responsibility of a notary for the deeds he makes that is attached throughout his life, thus demanding the application of the principle of prudence or thoroughness in every exercise of his authority. The principle of prudence is a legal obligation affirmed in the oath of office and laws and regulations in the field of notary, and has a strategic role in banking practices, especially in binding credit collateral in the form of Mortgage Rights on land. Negligence of a notary who also holds the position of Land Deed Making Officer (PPAT) in analyzing material collateral has the potential to cause legal defects in the deed, eliminate the executorial power of the collateral, and harm the bank and the debtor. This research aims to analyze the legal aspects of the application of the principle of prudence of notaries in banking credit guarantees and the resulting legal consequences. The research method used is normative juridical legal research, which positions law as the prevailing norm (law in books). The approaches employed include the statutory regulatory approach, the conceptual approach, and the case approach. Legal materials, including primary, secondary, and tertiary legal materials, were obtained through literature review and analyzed qualitatively and normatively through legal interpretation and reasoning. The research results show that the application of the principle of prudence by notaries and PPAT is an essential requirement in the preparation of bank credit guarantee deeds. Careful and comprehensive application of this principle results in a valid guarantee deed, has perfect evidentiary force, and provides legal protection for the bank and the debtor. Conversely, negligence in applying the principle of prudence can result in the deed being void or subject to cancellation, the loss of the guarantee's executorial power, and give rise to legal liability for the notary, both civil, administrative, and criminal.